A Two-Part Harmony: Changes in Peat Molecular Composition in Two Cores from an Ombrotrophic Peatland (Tremoal do Pedrido, Xistral Mountains, NW Spain) - Antonio Martínez Cortizas; Ainé Francos Golán; Mohamed Traoré; Olalla López-Costas (Soil Systems)
In peat research, the question often arises as to how similar/different the records of cores collected in the same mire are. This has been addressed for some metals (e.g., Pb and Hg), but the question remains open for the molecular composition of organic matter (pOM). Here, we explore this issue by analysing two cores from a raised bog, combining FTIR-ATR, mid-infrared (MIR) indices, and principal component analysis (PCA), and support the interpretation with multilinear regression (MLR) modelling of peat physical (colour) and elemental (C, N, and C/N) properties. The MIR indices and principal components showed depth patterns mainly related to long- and short-term peat decomposition, as well as other secondary changes involving some compounds (e.g., lignin). The depth records of the two cores are remarkably similar, indicating they were synchronously affected by the same processes and to almost the same degree. Cellulose crystallinity was the only property that showed differences in intensity. The good-to-excellent fitting of the MLR models supports the usefulness of FTIR-ATR in peat research. Further studies in a larger number of cores, from the same peatland and from different types of peatlands, are needed to better understand the spatio-temporal responses of the pOM and the factors involved.